2021
DOI: 10.1039/d0cy01958e
|View full text |Cite
|
Sign up to set email alerts
|

Reductase-catalyzed tetrahydrobiopterin regeneration alleviates the anti-competitive inhibition of tyrosine hydroxylation by 7,8-dihydrobiopterin

Abstract: l-Tyrosine hydroxylation by tyrosine hydroxylase is a significant reaction for preparing many nutraceutical and pharmaceutical chemicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…It was previously reported that the regeneration of BH4 promoted by DHPR derived from E. coli could help alleviate the anticompetitive inhibition of SrTH through 7,8-dihydrobiopterin (BH2). 14 However, the K m value for q-BH2 and NADH of bacterial DHPR is far higher than that of eukaryotic DHPR (Table S3). Given a YfkO nitroreductase in B. licheniformis similar to NprA nitroreductase, which is also classed as DHPR in Rhodobacter capsulatus, 37,38 it is speculated that YfkO may also play a role in the synthesis of BH4 by catalyzing q-BH2.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…It was previously reported that the regeneration of BH4 promoted by DHPR derived from E. coli could help alleviate the anticompetitive inhibition of SrTH through 7,8-dihydrobiopterin (BH2). 14 However, the K m value for q-BH2 and NADH of bacterial DHPR is far higher than that of eukaryotic DHPR (Table S3). Given a YfkO nitroreductase in B. licheniformis similar to NprA nitroreductase, which is also classed as DHPR in Rhodobacter capsulatus, 37,38 it is speculated that YfkO may also play a role in the synthesis of BH4 by catalyzing q-BH2.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…28 However, the two amino acid positions of SrTH should be replaced with Val126 and Phe203, which may reduce the affinity toward cofactor BH4. 14 In this study, the protein structure models of SrTH, SrTH V126L , SrTH F203Y , and SrTH V126L,F203Y were constructed, and the binding effects between the four proteins and the ligand BH4 were analyzed by Autodock 6.9 (Figure 1A−D). In the complex SrTH F203Y -BH4, there was another hydrogen bond (3.1 Å) formed between phenyl oxygen of Tyr203 and O-4 of BH4 (Figure 1B).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations